2023
DOI: 10.1002/adfm.202303225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reduction of Iodine Impurities and Defects with Potassium Formate for Efficient and Stable Perovskite Solar Cells

Abstract: The performance of perovskite solar cells (PSCs) is negatively affected by iodine (I2) impurities generated from the oxidation of iodide ions in the perovskite precursor powder, solution, and perovskite films. In this study, the use of potassium formate (HCOOK) as a reductant to minimize the presence of detrimental I2 impurities is presented. It is demonstrated that HCOOK can effectively reduce I2 back to I− in the precursor solution as well as in the devices under external conditions. Furthermore, the introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Very recently, Sun et al reported the use of potassium formate (HCOO − K + ) as an effective and oxygen-stable iodine reductant. 95 The study demonstrates that iodine formation within the precursor solution can be mitigated via the addition of formate anions yielding CO 2 and both I − and H + ions. These products are benign to the function of the PSCs enabling a high performance of 23.8% and good accelerated stability in ambient conditions.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Very recently, Sun et al reported the use of potassium formate (HCOO − K + ) as an effective and oxygen-stable iodine reductant. 95 The study demonstrates that iodine formation within the precursor solution can be mitigated via the addition of formate anions yielding CO 2 and both I − and H + ions. These products are benign to the function of the PSCs enabling a high performance of 23.8% and good accelerated stability in ambient conditions.…”
Section: Discussionmentioning
confidence: 89%
“…These products are benign to the function of the PSCs enabling a high performance of 23.8% and good accelerated stability in ambient conditions. 95…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the Shockley-Read-Hall model, it can be inferred (assuming uniform carrier distribution) that an enhancement in defect density will lead to an enhancement in the concentration of a series of deep level impurities. These deep level impurities not only become the recombination centers of electrons and holes, reducing the lifetime of charge carriers, but also become charged centers after ionization, causing scattering effects on charge carriers, hindering their migration, reducing the diffusion length of charge carriers, and reducing the conductivity of the device [65,66]. In addition, after introducing shallow level impurities into the device, the electrons or holes generated by ionization of shallow level impurities can transition to the corresponding CB or VB, which increases the number of carriers in the pn junction, enhances the strength of the built-in electric field and current density.…”
Section: R Np Nmentioning
confidence: 99%